Impact of a career guidance course on the career readiness of nursing students - Jeon, Jaehee; Koh, Jeong Rim (Edelweiss Applied Science and Technology, 2025)
This study aimed to confirm the impact of a career guidance course on the career preparation of nursing students. The study used a non-equivalent control group pre-post experimental design. The participants were 57 first-year students from a nursing college in W city, with 28 in the experimental group undergoing a career guidance elective and 29 in the control group not taking the course. Career preparation was assessed in terms of career decision-making level, career preparation behavior, and career decision-making self-efficacy. Data were collected from March to June 2024, with surveys administered before and after the 15-week course. The career guidance program was provided to the experimental group. Data analysis was conducted using SPSS 26.0, including frequencies, percentages, means, standard deviations, paired t-tests, and independent t-tests. The results showed that students who underwent the career guidance course had significant improvements in career decision-making, career preparation behavior, and career decision-making self-efficacy. Comparing the two groups, there were no significant differences in career decision-making, but significant differences were observed in career preparation behavior and career decision-making self-efficacy. Thus, to enhance nursing students' career preparation, it is necessary to develop and implement educational programs within the nursing curriculum that improve career decision-making, career preparation behavior, and self-efficacy. Moreover, it is recommended that such courses be actively developed and expanded to improve career readiness.